Designing English Pronunciation (EPRO) Android apps for Beginner Level - Luluk Choirun Nisak Nur; Jamaludin Jamaludin; Ulfa Wulan Agustina (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The ability of teachers and lecturers to understand and teach technology greatly affects the ability of students in the learning process. With the development of technology can improve the quality of education in schools. Therefore, the researcher aimed to design instructional media for and course students at the student and twelfth grade level. This study designs learning media through applications to learn English pronunciation in speaking skills at the beginner level. In this study using the Research and Development (R&D) method and through the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This learning media is called EPRO (English Pronunciation). This learning media is an audio designed to develop a product in the context of a feasibility test as an alternative learning media that can help students understand English Pronunciation in speaking skills. The research instrument was interviews with English tutors and the distribution of questionnaires to 13 students studying at AEC as a sample. The results of this study indicate that: (1) the media expert score is 4.44 (2) The material expert score is 4.57 (3) The product test result to students is 4.25 The researcher concludes that English Prounciation (EPRO) is suitable for use in the process learning speaking in class. From these results, there is a suggestion that the product be revised as suggested by the expert.